Digital Leadership in Educational Institutions: A Bibliometric Analysis using Scopus Database (2020 – 2025) - Ika Damayanti; Rugaiyah Rugaiyah; Desi Rahmawati; Kamaludin Kamaludin (FKIP - Universitas Riau, 2026)
The post-COVID-19 pandemic era and the rapid advancement of artificial intelligence (AI) have driven significant transformations in education; however, gaps remain in understanding the conceptual framework, trends, and scholarly collaboration of digital leadership, thus requiring a comprehensive analysis to identify current developments and future research directions. This study aims to analyze publication gaps, trends, and influential authors related to digital leadership in educational institutions using bibliometric analysis on the Scopus database for the period January 2020–January 2025. The data sources were Scopus journal articles selected through inclusion criteria and exclusion criteria, resulting in eight articles after the PRISMA flowchart process and manual selection. The analytical methods involved a descriptive review of study characteristics, identification of bias risks, and VOSviewer visualization for co-word and co-authorship mapping. The main findings reveal gaps in the integration of digital competence, Industry 4.0, and bibliometrics with digital leadership, highlight recent trends in digital learning environments, and identify influential authors such as Yuan Ying from global collaborations; the studies were dominated by mixed-methods in developing countries with sampling and local context biases. These conclusions underscore the need for a mature, inclusive, and human-centered digital leadership framework.